High throughput screening of key functional strains based on improving tobacco quality and mixed fermentation - Wen, Cai; Zhang, Qianying; Zhu, Pengcheng; Hu, Wanrong; Jia, Yun; Yang, Shuanghong; Huang, Yang; Yang, Zhen; Chai, Zhishun; Zhai, Tianyuan; Cao, Yu; Li, Dongliang (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract:[Background] Tobacco alcoholization is an important step in increasing the quality of tobacco leaf, which may convert a portion of low-grade tobacco leaves into useable product, however this may take to 2-3 years. The addition of exogenous microorganisms to tobacco leaves and treating them by biological fermentation can shorten the maturation time of tobacco leaves, and improve the quality and applicability of low-grade tobacco leaves. [Methods] Several strains were screened from low-grade tobacco by flow cytometry, including the bacteria Bacillus amyloliticus, with starch degradation ability and Bacillus kochii, with protein degradation ability, and the fungus Filobasidium magnum with lipid oxidase ability, and were inoculated onto tobacco leaves, both individually and in combination, for solid-state fermentation. [Results]The greatest improvement in tobacco quality was observed when strains 4# and 3# were applied at a ratio of 3:1. The Maillard reaction products, such as 2-amyl furan, 1-(2-furanmethyl) -1h-pyrrole, furfural and 2, 5-dimethylpyrazine, were significantly increased, by up to more than 2 times. When strains F7# and 3# were mixed at a ratio of 3:1, the improvement of sensory evaluation index was better than that of pure cultures. The increase of 3-(3, 4-dihydro-2h-pyrro-5-yl) pyridine, β -damasone and benzyl alcohol was more than 1 times. The increase of 2-amyl-furan was particularly significant, up to 20 times. [Conclusion]The functional strains screened from tobacco leaves were utilized for the biological fermentation of tobacco leaves, resulting in the reduction of irritation and an improvement in quality of final product, showing a good potential for application.